Integration of Computational Thinking in Natural and Social Science Learning in Elementary Schools to Improve Problem-Solving Skills - Anna Roosyanti,; Diyas Age Larasati, (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2026)
Mastery of 21st century skills is very necessary in facing the development of the industrial revolution 4.0 era, one of which is computational thinking. Computational thinking is the ability to think systematically, logically, and structured to solve problems. This is very relevant to the learning of Natural and Social Sciences (IPAS) in Elementary Schools. This study aims to explain computational thinking, its integration in IPAS learning, its benefits in improving problem-solving skills of Elementary School students, identify its implementation strategies, and analyze challenges and opportunities in its application. The research method used is a literature study with a descriptive approach through the analysis of various national and international journal articles indexed by Sinta and Scopus. The results of the literature review indicate that the integration of computational thinking in IPAS learning in Elementary Schools makes a real contribution to improving students' problem-solving skills. Through a hybrid approach that combines plugged and unplugged approaches, it is the most appropriate strategy to be implemented in Elementary Schools in Indonesia. However, there are still challenges in its implementation including limited teacher understanding of computational thinking, limited technological infrastructure, and contextual and problem-based learning design. Kata kunci: Computational thinking, IPAS, Sekolah Dasar, Keterampilan Pemecahan Masalah